ETHNIC PROFILING AND COUNTERTERRORISM IN EUROPEAN HUMAN RIGHTS REGIME: A PHILOSOPHICAL LEGAL REVIEW - Mahaarum Kusuma Pertiwi (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThis essay will analyze the European Union framework of ethnic profiling in the aim of combating terrorism that will be contrasted to the principle of non-discrimination that is fundamental in the European regime of Human Rights. Research question in this essay is whether the European human rights regime consistently holds the principle of non-discriminatory in justifying the use of ethnic profiling in combating terrorism. IntisariMakalah ini akan membahas mengenai kebijakan profil etnis (ethnic profiling) dalam rangka memerangi terorisme di Uni Eropa yang akan dikontraskan dengan prinsip non-diskriminasi yang juga merupakan hal penting dan mendasar dalam perlindungan Hak Asasi Manusia di Eropa. Permasalahan mendasar yang dikaji dalam studi ini adalah apakah Uni Eropa konsisten dalam memegang prinsip non-diskriminasi ketika membenarkan penggunaan kebijakan profil etnis dalam memberantas terorisme.